2011
DOI: 10.1111/j.1742-7843.2011.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mealtime Insulin Aspart and Bedtime NPH Insulin on Postprandial Inflammation and Endothelial Cell Function in Patients with Type 2 Diabetes

Abstract: Acute hyperglycaemia exerts deleterious effects on the arterial wall. We suggested that rapid-acting insulin has a beneficial postprandial effect on endothelial dysfunction and inflammation compared with intermediate-acting insulin because of its ability to lower postprandial hyperglycaemia. This was tested in a parallel, controlled study on well-controlled patients with type 2 diabetes randomly assigned to bedtime Neutral Protamine Hagedorn (NPH) insulin (n = 41) or mealtime insulin aspart (n = 37). They were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 33 publications
(52 reference statements)
1
9
0
Order By: Relevance
“…Ceriello et al suggested that insulin dampens the effect of hyperglycaemia on FVII [14]. In our study, the postprandial total insulin levels (AUC and postprandial mean) were comparable in the two insulin groups [20] and might affect concentrations of FVII, D‐dimer and F1+2 to a similar extent. Equal insulin levels can also explain why the two insulin regimens had similar effects on fibrinolysis [18,19], and we observed highly significant correlations between the insulin response (AUC and postprandial mean) and the PAI response in both treatment groups (not shown).…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Ceriello et al suggested that insulin dampens the effect of hyperglycaemia on FVII [14]. In our study, the postprandial total insulin levels (AUC and postprandial mean) were comparable in the two insulin groups [20] and might affect concentrations of FVII, D‐dimer and F1+2 to a similar extent. Equal insulin levels can also explain why the two insulin regimens had similar effects on fibrinolysis [18,19], and we observed highly significant correlations between the insulin response (AUC and postprandial mean) and the PAI response in both treatment groups (not shown).…”
Section: Discussionsupporting
confidence: 63%
“…The beneficial effect of reducing postprandial glucose on clinical endpoints was recently questioned in a randomised controlled trial (HEART2D) showing that the risk of future CVD is similar, when either mealtime insulin or bedtime insulin is used as secondary prevention in type 2 diabetes patients experiencing a recent acute myocardial infarction [29]. In line with this, the CVD risk markers vWF, fibrinogen, ICAM and CRP are affected equally in the postprandial state by insulin aspart and insulin NPH in spite of significantly different effects on postprandial glucose concentrations [20]. We suggest here that this is also the case for coagulation and fibrinolysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations